Investigation on temperature-dependent electrical properties of La1−xAxCoO3 (A – La, Li, Mg, Ca, Sr, Ba). Issue 1 (29th November 2019) - Muraleedharan, Sreepriya; Thiruvenkatam, Vijayaraghavan; Karayi, Simya Olavil; Karuppiah, Kavitha; Jawahar, Vigneshwaran; Ashok, Anuradha M.
Abstract : Surface of the sintered pellet of LaCoO3 and Cole–Cole plot revealing the contribution from grain and grain boundary on its electrical properties. Abstract : This study focuses on temperature-dependent electrical property investigation of undoped and defect induced A (La) site-doped LaCoO3 with Li, Mg, Ca, Sr and Ba synthesized by a sol–gel method. X-ray diffraction analysis of the samples revealed a phase pure rhombohedral crystal structure with slight change in unit cell parameters, indicating the successful incorporation of the dopants. HRTEM analysis of the samples revealed the polycrystalline nature of the samples. Warpage-free, well-sintered dense ceramic pellets as revealed by SEM images were further analyzed using impedance spectroscopy. Temperature-dependent electrical studies showed a significant variation in resistance with the increase in temperature in all studied perovskites. The Cole–Cole plot showed a clear contribution of grains and grain boundaries of the materials to the electrical conductivity which was further analyzed using modulus spectroscopy. The Arrhenius plot drawn for all the studied compositions clearly indicated that doping alkali and alkaline earth metals improves the electrical conductivity of LaCoO3 . Among the dopants, calcium and barium substitution resulted in maximum enhancement in conductivity in the range of 9 × 10 −8 –8 × 10 −4 S cm −1 from 300 to 750 °C.